THE IDEA OF ISLAMIZATION: A Study of Imam Suprayogo’s Thought (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
Modern science has been marred by lingering problems andconsequences, as twentieth-century critics like Theodor Adorno andSeyyed Hossein Nasr argued that modern science has been emptied ofspiritual values and increasingly disconnected from ethical religiousconcerns. As a result, most scientists adhere to the dichotomy betweenscience and religion, implying not only distinction, but also separationand contradiction. Equally problematic is the widely held, but naïve, viewthat science is neutral and value-free, has no human, economic, political,military, national, industrial or commercial interests. In the wake ofrealization that modern science could be harmful and detrimental to theminds and lives of Muslim. Calls for Islamization was launched acrossthe Muslim world from Virginia to Casablanca. This article aims to assessthe idea of Islamization of contemporary science as espoused andelaborated by Imam Suprayogo, a former rector of the State IslamicUniversity (UIN) in Malang, Indonesia. Based on library research, thisstudy found that Imam Suprayogo’s idea of Islamization prescribesintegration of science and religion to eradicate the long-held dichotomybetween the two, particularly between scientific claims and Islamicdoctrines. Imam Suprayogo also proposed to reconstruct a religiousscientific paradigm by introducing the “tree of knowledge” andlaunching the “Tarbiyah Ulul Albab” (education of the Intelligentsia)which has been implemented during his term in an attempt to transformUIN Malang into an Islamic educational institution that teaches bothscience and religion while at the same time projecting the Islamic values.Ilmu pengetahuan modern saat ini, telah dirusak oleh sejumlah masalahdan konsekuensi yang tidak diinginkan, sebagaimana kritikus abad keduapuluh seperti Theodor Adorno dan Seyyed Hossein Nasr menyatakanbahwa ilmu pengetahuan modern telah dikosongkan dari nilai-nilaispiritual dan terputus dari masalah etika keagamaan. Akibatnya, sebagianbesar ilmuwan menganut dikotomi antara ilmu dan agama, hal tersebuttidak hanya perbedaan, tetapi juga pemisahan dan kontradiksi di antarakeduanya. Masalah yang sama datang dari pandangan secara luas, tetapinaif, bahwa ilmu itu netral dan bebas nilai, tidak memiliki kepentinganmanusia, ekonomi, politik, militer, nasional, industri atau komersial.Tanpa disadari bahwa ilmu pengetahuan modern bisa berbahaya danmerugikan pikiran serta kehidupan Muslim. Adapun seruan untukIslamisasi telah diluncurkan ke seluruh dunia Muslim dari Virginia hinggaCasablanca. Artikel ini bertujuan untuk mengkaji gagasan Islamisasi ilmupengetahuan kontemporer sebagaimana dianut dan dielaborasi olehImam Suprayogo, mantan rektor Universitas Islam Negeri (UIN)Malang, Indonesia. Berdasarkan studi pustaka, penelitian ini menemukanbahwa gagasan Islamisasi Imam Suprayogo mengatur integrasi ilmu danagama untuk menghapus dikotomi yang telah lama ada di antarakeduanya, khususnya antara klaim ilmiah dan doktrin Islam. ImamSuprayogo juga mengusulkan untuk merekonstruksi paradigma keilmuanagama dengan memperkenalkan “pohon ilmu” serta meluncurkanprogram “Tarbiyah Ulul Albab” yang telah dilaksanakan selamaistilahnya dalam upaya mentransformasi UIN Malang menjadi lembagapendidikan Islam yang mengajarkan ilmu pengetahuan dan agamasekaligus memproyeksikan nilai-nilai Islam.